Microsatellite-based genetic characterization of the indigenous Katjang goat in Peninsular Malaysia - Mohd Adhan, Ernie Muneerah; Md Tamrin, Nur Aida; Salisi, Mohd Shahrom; Zulkifly, Shahrizim; Ghazali, Siti Shaidatul Maisarah; Temuli, Jackson Jenun; Rosali, Mohd Hifzan; Nazari, Shariffah; Wan Nik, Wan Mohd Kamil; Kamalludin, Mamat Hamidi (MDPI, 2021)
The Katjang goat is the only indigenous domestic goat breed in Malaysia. Following a national baseline survey from 2001 to 2002, this breed was reported to the FAO as being at risk of extinction. In this study, 36 microsatellite markers were screened, and 25 polymorphic markers were used to analyze the genetic structure of the Katjang goat breed in Peninsular Malaysia. A sample set of data derived from another 10 populations from three published research studies was used as an outgroup for an inter-population genetic study. The analysis showed that the mean value of the observed heterozygosity was 0.29 ± 0.14, and the expected heterozygosity was 0.72 ± 0.14, which indicated low genetic diversity. The inbreeding coefficient, FIS, was high, at 0.46. Significant (p < 0.01) deviations from the Hardy Weinberg equilibrium were noted for all loci. The bottleneck analysis using the Wilcoxon Rank test under the two-phase model of mutation was significant (p < 0.01) for heterozygosity excess, which suggested that the Katjang breed had undergone significant population reduction in the past. Through combined analysis of data from publicly available research, almost the entire population of Katjang goats represent the centroid and are grouped together on a multidimensional scaling plot, except for the Terengganu population. Network analysis revealed that the goat population from Pahang formed the centrality of the network.